Back Cover Image, Volume 92, Number 9, September 2020. Issue 9 (16th August 2020) - Mo, Chunbao; Tan, Dechan; Mai, Tingyu; Bei, Chunhua; Qin, Jian; Pang, Weiyi; Zhang, Zhiyong
Abstract : Back Cover Caption : The cover image is based on the Research Article An analysis of spatiotemporal pattern for COIVD‐19 in China based on space‐time cube by Chunbao Mo et al., https://doi.org/10.1002/jmv.25834 .